Liver CT 검사에서 프로토콜 변화에 따른 선량 감소와 영상의 질 개선에 관한 연구 - 조유진(Yu Jin Cho); 조평곤(Pyong Kon Cho) (방사선기술과학, 2015)
The purpose is reducing radiation dose while maintaining of image quality in liver dynamic CT(LDCT) scan, by protocols generally used and the tube voltage set at a low level protocol compared to the radiation dose and image quality. The target is body mass index, 18.5~24 patients out of 40 patients who underwent the ACT(abdominal CT). Group A(tube voltage : 120kVp, SAFIRE strength 1) of 20 people among 40 people, to apply the general abdominal CT scan protocol, group B(tube voltage : 100kVp, apply SAFIRE strength 0~5) was 20 people, set a lower tube voltage. Image quality evaluation was setting a region of interest(ROI) in the liver parenchyma, aorta, superior mesenteric artery (SMA), celiac trunk, visceral fat of arterial phase. In the ROI were compared by measuring the noise, signal to noise ratio(SNR), contrast to noise ratio(CNR), CT number. In addition, qualitative assessments to evaluate two people in the rich professional experience in Radiology by 0-3 points. We compared the total radiation dose, dose length product(DLP) and effective dose, volume computed tomography dose index(CTDIvol). The higher SAFIRE in the tube voltage 100 kVp, noise is reduced, CT number was increased. Thus, SNR and CNR was increased higher the SAFIRE step. Compared with the tube voltage 120kVp, noise, SNR, CNR was most similar in SAFIRE strength 2 and 3. Qualitative assessment SAFIRE strength 2 is the most common SAFIRE strength 2 the most common qualitative assessment, if the tube voltage of 100kVp when the quality of the images better evaluated was SAFIRE strength 1. Dose was reduced from 21.69%, in 100kVp than 120kVp. In the case of a relatively high BMI is not LDCT scan, When it is shipped from the factory tube voltage is set higher, unnecessary radiation exposure when considering the reality that is concerned, when according to the results of this study, set a lower tube voltage and adjust the SAFIRE strength to 1 or 2, the radiation without compromising image quality amount also is thought to be able to be reduced. 간 역동적 CT(Liver Dynamic Computed Tomography; LDCT) 검사에서 일반적으로 사용하는 프로토콜과 관전압을 낮게 설정한 후 프로토콜을 변화시켰을 때 방사선량과 영상의 질을 비교하여 영상의 질을 유지하면서 방사선량을 감소시킬 수 있는 방안을 알아보고자 하였다. LDCT를 시행한 환자 중 신체질량지수(body mass index; BMI)가 18.5~24인 환자 40명을 대상으로 일반적인 복부 CT 검사 프로토콜을 적용한 A그룹 20명(관전압: 120 kVp, SAFIRE strength1)과 관전압을 낮게 설정한 B그룹 20명(관전압: 100 kVp, SAFIRE strength 0~5 적용)이었다. 영상의 질 평가는 동맥기의 간 실질 조직, 대동맥, 상장간막동맥, 복강동맥, 내장지방 그리고 백그라운드에 관심영역(region of interest; ROI)을 설정해 잡음(noise), 신호대 잡음비(signal to noise ratio; SNR), 대조도 대 잡음비(contrast to noise ratio; CNR), CT number를 측정 비교하였다. 또한 정성적 평가는 경험이 풍부한 영상의학과 전문의 2명이 0~3점까지로 평가하였다. 방사선량은 총 DLP(dose length product)와 유효선량, CTDIvol(volume computed tomography dose index)을 비교하였다. 관전압 100 kVp에서 SAFIRE가 높을수록 잡음은 감소하고, CT number는 증가하였다. 따라서 SNR과 CNR은 SAFIRE 단계가 높을수록 증가하였다. 관전압 120 kVp와 비교하여 잡음, SNR, CNR이 SAFIRE strength 2, 3에서 가장 유사하였다. 정성적 평가는 SAFIRE strength 2가 가장 많았고 관전압이 100 kVp일 때 영상의 질이 더 좋다고 평가한 경우는 SAFIRE 1이었다. 방사선량은 120 kVp에 비해 100 kVp에서 21.69% 감소하였다. BMI가 비교적 높지 않은 LDCT 검사의 경우 공장에서 출고될 당시에 관전압이 높게 설정되어 있어 불필요한 방사선피폭이 우려되고 있는 현실을 고려하면, 본 연구 결과에 따라 관전압을 낮게 설정하고 SAFIRE strength를 2로 조정하면 영상의 질 저하 없이 방사선량도 감소시킬 수 있을 것으로 사료된다.